Peran Electronic Word of Mouth sebagai Strategi Komunikasi Pemasaran pada Produk Avoskin - Nasution, Nurul Fadilah; Prasetya, Hendri; Khohar, Abdul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Communication strategy for Avoskin products, a beauty brand based in Indonesia. The research method used is qualitative with a case study approach. Data was collected through analysis of e-WOM content on social media as well as documentation studies related to Avoskin's marketing strategy. The research results show that Avoskin has succeeded in building a reputation as a high-quality and sustainable beauty brand. By focusing on innovation, product quality and effective communication via social media, Avoskin can reach and build strong relationships with its consumers, especially women aged 18 to 34 who care about the environment and natural ingredients. Marketing strategies focusing on product quality, informative communication, and commitment to sustainability have helped Avoskin gain recognition and awards in the Indonesian beauty industry. Even though it faces the challenges of increasingly fierce competition, Avoskin has the opportunity to expand its market and increase its visibility locally and globally. Avoskin's success proves that local brands can compete and excel in the global market with dedication, innovation and commitment to quality and sustainability.